The changing contours of government - Thomas R. Cusack (Wissenschaftszentrum Berlin für Sozialforschung (WZB); Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1991)
This paper examines the development of general government finance and employment within fifteen industrialized democracies during the post-World War II era. Annual time series, extending, where possible, from 1950 through 1988, are analyzed (as well as detailed in the appendix to the paper). Using a variety of accounting schemes, the changing contours of government's control over economic resources are described. It is pointed out that while the growth in government spending relative to GDP has slowed down during the 1980's, the general inability or unwillingness to accelerate the growth in revenues has led in many cases to a significant increase in public debt. This has been accompanied by a squeeze on many spending items, particularly in the area of investment, as interest payments on the debt absorb more and more funds. While growth in government employment has continued, though at a slower pace than in the decades of the '60's and 70's, there has been some marked progress in bringing the cost of public employment into line with what is occurring in the private sector. This latter development is symptomatic of the convergence in price movements that has occurred; during the last decade or so governments have not continued to leap ahead of the private sector, particularly households, in terms of rising costs. – – Dieser Beitrag untersucht die Entwicklung von offentlichen Finanzen und offentlicher Beschaftigung in funfzehn industrialisierten Demokratien seit dem 2. Weltkrieg. Es werden Zeitreihen mit jahrlichen Daten - soweit moglich von 1950 bis 1988 - analysiert und im Anhang ausfuhrlich dargestellt. Anhand einer Vielzahl von Berechnungsschemata werden die sich verandemden Umrisse staatlicher Kontrolle uber wirtschaftliche Ressourcen beschrieben. Obwohl sich das Wachstum staatlicher Ausgaben relativzum BIP in den '80er Jahren verlangsamte, hat der allgemeine Mangel an Moglichkeit oder Bereitschaft, die Einnahmen zu steigem, in vielen Fallen zu einer signifikanten Zunahme der offentlichen Verschuldung gefuhrt. Da Zinszahlungen auf die Schulden immer mehr Mittel in Anspruch nehmen, ging dies einher mit Einsparungen in vielen Ausgabereichen, besonders bei den Investitionen. Wahrend sich die Zunahme der offentlichen Beschaftigung fortgesetzt hat, wenn auch langsamer als in den '60er und 70er Jahren, hat ein deutlicher Fortschritt bei der Angleichung der staatlichen an die privatwirtschaftlichen Beschaftigungskosten stattgefunden. Die letztere Entwicklung spiegelt sich in der Konvergenz der Preisbewegungen wieder; kostenmaBig laufen die offentlichen Hande dem privaten Sektor nicht mehr davon, insbesondere nicht den privaten Haushalten.
Keywords: 320